Feminism Campaign On Social Media: Analysis of Indonesian Female Youtuber Movement - Shela Monica; Z Hidayat; Dyah Meita Nugraheni; Chel'en Christevelyn Dewi (Syntax Literate, 2022)
Women are a minority and oppressed. Women deserve to have the same rights that are obtained and owned by men. There is gender inequality between women and men in society (gender inequality). This paper aims to analyze the support and campaigns on feminism carried out by the digital activist community who support equality on blogs and social media. The research method is carried out with a phenomenological qualitative approach by observing, interviewing community leaders and their members, and analyzing content on social media. The dimensions of the analysis are related to the perspective of feminism and gender equality with the struggle channel on social media. This research shows that the community has a feminist spirit in the struggle through social media, but their voices are still a minority in the community structure. Women's advocacy is carried out in the face of violence, especially sexual harassment, which is also reflected in interactions on social media. The community carried out a persuasive struggle for rights and equality, but the primary culture's climate has not supported their effort. Through social media channels, the community seeks to reduce the stereotype of the position and role of women. It is still facing challenges from the social awareness of the dominant community group.